Analisis Semiotika Iklan E-Commerce “Dekatkan Yang Jauh, Kirim Yang Bermakna” di Media Sosial - Kurnia Ramadhan; Rosita Anggraini (UNISBA Press, 2023)
Abstract. The purpose of this study was to examine the meaning of Tokopedia's ad